Diffusion Coefficients of Copper Chloride in Aqueous Solutions at 298.15 K and 310.15 K - Ribeiro, Ana C. F. (2005)
Mutual diffusion coefficients (interdiffusion coefficients) and molar conductivities have been measured for copper(II) chloride in water at 298.15 K and 310.15 K at concentrations between 0.005 mol·dm-3 and 0.05 mol·dm-3. The diffusion coefficients were measured using a conductometric cell. The experimental data are discussed on the basis of the Onsager−Fuoss model. The Nernst diffusion coefficients derived from diffusion (1.297 × 10-9 and 1.690 × 10-9) m2·s-1 and from conductance (1.282 × 10-9 and 1.663 × 10-9) m2·s-1 at two temperatures (298.15 K and 310.15 K, respectively) are in good agreement.